Advanced Censoring Schemes for Statistical Inference of Reliability in Engineering Contexts (European Journal of Pure and Applied Mathematics, 2025)
In practice, systems that are exposed to rigorous operational environments commonly malfunction. Researchers have yet to fully examine the crucial idea that system failure frequently occurs when these strict operating constraints are reached. This study covers this gap in an analysis of the multi-stress-strength model $Υ=P(U